FOUNDATION ALTERNATIVES IN DREDGE FILL SOILS OVERLAYING ORGANIC CLAY - M. S. Islam; M. Nasrin; A. J. Khan (International Association of Lowland Technology, 2013)
Dhaka city has experienced a rapid growth or urban population for the last 40 years. this high population increase demands rapid expansion are already eshausted. As such new areas are being reclaimed by both government and private agencies using dredge fill from nearby river sources. Sub-soil investigations have been carried out in different reclaimed areas within the city. It is found that top filling layer is non-plastic fine sand. Mean grain size of which varies from 0.15 to 0.20 mm. A very soft organic layer exists below the filling layer which is highly plastic and highly compressible. Field SPT N-value of filling layer and organic layer vary from 2 to 11 and 1 to 2, respectively. Attempts have been made to correlate unconfined compressive strenght with SPT N-value, plasticity index, and organic content. Attempts have also been made to correlate compression index with organic content and initial void ratio of the soft organic clay. The correlations of the soil properties with organic content are variable and in most of the cases no definite correlations could be established. It has been observed that filling sand overlaying organic layer will badly affects the foundation on or having in it. Foundation alternatives have been suggested for the reclaimed areas in Dhaka city.